2005
DOI: 10.1097/00007632-200501010-00023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Functional Rating Index and the 18-Item Roland-Morris Disability Questionnaire: Responsiveness and Reliability

Abstract: The Functional Rating Index seems preferable to the 18-item Roland-Morris Disability Questionnaire for use in clinical trials and clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 30 publications
6
30
0
Order By: Relevance
“…44 A comparative study 34 of the 24-item version with both the 18-and 23-item versions showed equivalent sensitivity, reliability, and possibility of refl ecting the disability; thus, the original 24-item RMDQ was recommended. Chansirinukor et al 45 found that the RMDQ-18 was less responsive and reliable than the Functional Rating Index, and ascribed this to reduction of reliability and loss of information with the use of a yes/no response option suggested by Streiner and Norman. 46 The original version of the RMDQ was initially developed to assess disability secondary to axial LBP, but we still use the 24-item RMDQ for patients who have radiating leg pain.…”
Section: Discussionmentioning
confidence: 99%
“…44 A comparative study 34 of the 24-item version with both the 18-and 23-item versions showed equivalent sensitivity, reliability, and possibility of refl ecting the disability; thus, the original 24-item RMDQ was recommended. Chansirinukor et al 45 found that the RMDQ-18 was less responsive and reliable than the Functional Rating Index, and ascribed this to reduction of reliability and loss of information with the use of a yes/no response option suggested by Streiner and Norman. 46 The original version of the RMDQ was initially developed to assess disability secondary to axial LBP, but we still use the 24-item RMDQ for patients who have radiating leg pain.…”
Section: Discussionmentioning
confidence: 99%
“…The FRI score was calculated as follows: (total score/40) × 100%. The FRI is known for its reliability, validity, and responsiveness and recently found preferable to the well-known 18-item Roland-Morris Disability Questionnaire for use in clinical trials and practice [29]. A FRI of ≥30% perceived disability was used in the analyses as a stringent definition for LBP, and the mere presence of back pain at the time, was used as an inclusive definition to record cases of LBP.…”
Section: Case Definitionmentioning
confidence: 99%
“…The mean (SD) total score of RMDQ was 10.8 (5.7); most participants had persistent LBP (73.1% of the total sample), and the mean (SD) pain score on a 0-10 NRS was 6.1 (2.1) ( Table 2). As three studies [23][24][25] did not include a question on pain intensity, relationships between pain intensity and sleep disturbance were examined for a sub-group of 1,511 patients from 11 studies. The process of data extraction is shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Individual patient data were extracted from 13 studies previously conducted by the authors or their colleagues between 2001 and 2009 [22][23][24][25][26][27][28][29][30][31][32]. Studies were eligible for inclusion if they contained the ''I sleep less well because of my back'' item of the Roland and Morris Disability Questionnaire (RMDQ).…”
Section: Methodsmentioning
confidence: 99%